2019
DOI: 10.1002/cbf.3446
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts promote malignancy of gastric cancer cells via Nodal signalling

Abstract: The roles of cancer‐associated fibroblasts (CAFs) in progression of gastric cancer (GC) are far from well illustration. Here, we show that CAFs can trigger the proliferation and decrease the doxorubicin (Dox) sensitivity of GC cells via secretion of Nodal, one embryonic morphogen that can promote malignancy of various cancers. The neutralization antibody of Nodal can attenuate CAFs‐induced cell proliferation. Further, CAFs can activate the Smad2/3 signal, which further increase the phosphorylation and nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Mechanistically, in gastric cancer, a neutralizing antibody against Nodal attenuated CAF-induced cancer cell proliferation through Nodal-induced activation of the Smad2/3/AKT signal axis. 139 In another study, blockade of PTEN phosphorylation by siRNA led to the promotion of colon cancer cell proliferation upon stimulation with CXCL12 through the activation of PI3K/AKT signaling pathway. 140 In contrast, Subramaniam et al found that a specific PI3K inhibitor (LY294002) reversed the CAF-mediated cell proliferation in endometrial cancer.…”
Section: Major Signaling Pathways and Targeted Therapies In Cafsmentioning
confidence: 97%
See 1 more Smart Citation
“…Mechanistically, in gastric cancer, a neutralizing antibody against Nodal attenuated CAF-induced cancer cell proliferation through Nodal-induced activation of the Smad2/3/AKT signal axis. 139 In another study, blockade of PTEN phosphorylation by siRNA led to the promotion of colon cancer cell proliferation upon stimulation with CXCL12 through the activation of PI3K/AKT signaling pathway. 140 In contrast, Subramaniam et al found that a specific PI3K inhibitor (LY294002) reversed the CAF-mediated cell proliferation in endometrial cancer.…”
Section: Major Signaling Pathways and Targeted Therapies In Cafsmentioning
confidence: 97%
“…3 ). The fact that PI3K/AKT signaling pathways regulated CAF-mediated cancer cell proliferation in oral, 136 lung, 137 , 138 gastric, 139 colon, 140 endometrial, 141 and anal 142 cancers. Mechanistically, in gastric cancer, a neutralizing antibody against Nodal attenuated CAF-induced cancer cell proliferation through Nodal-induced activation of the Smad2/3/AKT signal axis.…”
Section: Major Signaling Pathways and Targeted Therapies In Cafsmentioning
confidence: 99%
“…Desmoplasia refers to the growth of excessive stromal tissue around tumours, and fibroblasts located in this stromal tissue, termed cancer-associated fibroblasts (CAFs), are key players in the cancer stroma. The critical roles of CAFs have been investigated recently in various types of cancer [5][6][7][8]. CAFs promote angiogenesis via the production of pro-angiogenic factors such as fibroblast growth factor 2 (FGF2) and vascular endothelial growth factor A (VEGFA) and contribute to immune surveillance in tumour cells by recruiting immunosuppressive cells such as myeloid-derived suppressor cells (MDSCs) and M2 macrophages [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NODAL expression is inversely correlated with susceptibility to gamma delta (γδ) T cell cytotoxicity, at least in part through decreased surface expression of the immune activating danger signal MHC class I polypeptide-related sequence A/B (MICA/B) 50 . CAFs from a gastric cancer mouse model have recently been shown to promote cancer cell proliferation and resistance to doxorubicin via NODAL secretion 51 and NODAL appears to induce CAF-like phenotypes in mouse and human fibroblast cell lines 52 . The extent to which NODAL may affect CAF phenotypes in the breast TME has not, however, been explored.…”
Section: Introductionmentioning
confidence: 99%